Investigation of the influence of nanoparticles of metals on fermenttation of wort of high concentrations - Kovalchuk, Svitlana; Shiyan, Peter; Mudrak, Tatiana; Kuts, Anatoly; Kyrylenko, Roman (My University, 2017)
There was theoretically grounded and experimentally proved the expedience of enriching high-concentrated wort of the starch-containing raw material with such additional source of mineral nutrition for yeast cells as nanoparticles of metals. There was studied the influence of nanoparticles of metals on hydrolysis of biopolymers of the raw material and biosynthesis of organic compounds at wort fermentation. It was experimentally established, that the most positive influence of biosynthetic properties of yeast cells is realized by zinc and magnesium. At using zinc and magnesium, yeast biomass and alcohol content in mashes increase. Best chemical-technological indices of mashes were received at adding nanoparticles of zinc and magnesium at the stage of batch dilution.There was experimentally studied the synthesis of volatile organic admixtures in marsh distillates depending on point of adding nanoparticles of metals. Теоретично обґрунтовано та експериментально підтверджено доцільність збагачення високонцентрованого сусла із крохмалевмісної сировини додатковим джерелом мінерального живлення для дріжджових клітин, в якості наночастинок металів. Досліджено вплив наночастинок металів на гідроліз біополімерів сировини та біосинтез органічних сполук при зброджуванні сусла. Експериментально встановлено, що найбільш позитивний вплив на біосинтетичні властивості дріжджових клітин має цинк та магній. При застосуванні цинку та магнію біомаса дріжджів та вміст спирту в бражках зростає. Найкращі хіміко-технологічні показники бражок отримані при додаванні наночастинок цинку та магнію на стадії розрідження замісу. Експериментально досліджено синтез летких органічних домішок в бражних дистилятах залежно від точки внесення наночастинок металів
Keywords: yeast cell; wort; alcohol marsh; nanoparticles of metals; marsh distillate; дріжджові клітини; сусло; спиртова бражка; наночастинки металів; бражні дистиляти; кафедра готельно-ресторанної справи; кафедра біотехнології продуктів бродіння і виноробства